Pengaruh Air Rebusan Daun Sirih Dalam Menurunkan Keluhan Flour Albus Pada Wanita Usia Subur Di Desa Serakat Jaya - Mariana Mariana; Winarni Winarni (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: Reproductive and sexual health is the right of an individual, family and society regardless of status, race, age, gender, religion, sexual orientation, economics and social status. According to data from the 2019 Indonesian Demographic and Health Survey (SDKI), in Indonesia, one of the complaints frequently encountered in clinics and maternal and child health (KIA) is vaginal discharge/fluor albus. Efforts to reduce vaginal discharge can be done by means of pharmacological therapy (drugs) or non-pharmacological therapy, one of which is using boiled water from betel leaves. Betel leaves contain essential oils consisting of betlephenol, kavikol, sesquiterpenes, hydrocicavicol, cavibetol, estragol, eugenol, and carvacrol, and among these substances are kavikol, euginol and ethanol which can be used to treat vaginal discharge. Objective: To determine the effect of boiled betel leaf water to reduce complaints of flour albus in women of childbearing age. Research Location : This research was conducted in the village of Serakat Jaya on 32 women of childbearing age who experienced vaginal discharge. Research Method : The research design used was a pre-experimental design type one group pretest-posttest (initial test, single group final test). The data analysis used was the Wilcoxon Signed Rank Test. Results : The research shows a p-value < 0.001 p < 0.05 which shows that boiled water from betel leaves has an effect on reducing complaints of flour albus.